COMMUNICATION FOR PEACE AND RESILIENCE IN ASSOCIATIONS OF VICTIMS OF THE ARMED CONFLICT (Encuentros, 2021)
This article proposes outcomes for the extension project referred as ‘the communication for social change in the community education of the armed conflict victim associations in the municipality of La Playa Belen, Norte de Santander, which aimed to develop communicative strategies for peace building, resilience as well as community education for these armed conflict victim associations in this area known as Catatumbo in Colombia. This research has been based on a qualitative methodology and research-action model, by using information collection techniques such as literature review, focus groups and seni-structured interviews through which an updated diagnostic could be carried out on the socio-economic conditions of the associations settled in this municipality in order to develop strategic actions which allowed to create a scenario for peace and social change. Some of the most relevant results have shown that these social groups need to be educated on a steady basis on different topics such as leadership, team work, community self-management, community organization, citizen participation, and community project or proposition formulation to come up with socio-economic propositions as solution alternatives for the problems which have been identified as a result of the armed conflict that have affected their lives in addition to both physical and symbolic reparation which allow to rebuild governmental trust, social fabric and also the realization of a peaceful territory..
Keywords: Communication, Peace, Social Change, Training, Resilience.